I Dream, Therefore I Am: What Dreams May Come - Schwartz, Susan L. (The journal of religion and film, 2000)
In the ultimate sense of "projection" as psychological and ontological creation, this film proposes that imagined reality is the only reality after death. The imagery we are given is primarily European. The theology, however, owes less to western sources and more to eastern concepts. This film treats some remarkably serious religious issues, such as guilt, suffering, transformation, transmigration, and the essence of the immortal soul. One overriding idea that pervades its presentation is the ancient formulation by South Asian traditions of Maya, that generates the world that we know while simultaneously assuring us that it is an illusion. What Dreams May Come is a work of imagination (film) about a work of imagination (life and death), constructing a western illusion about an eastern illusion, all the while addressing western apolcalyptic paranoia at the end of the millennium, which is, of course, irrelevant in the east. This essay explores the ways in which the film appropriates and translates such ideas, and reflects upon the causes and effects such usage implies.